Estudio comparativo de la implementación de una aplicación web o de escritorio para el control del personal de la empresa AMESEPREVE en la ciudad de Babahoyo. - Dorado Gutierrez, Margarita Elizabeth (2020)
This case study describes the comparative process of a web application and a desktop application for the company AMESEPREVE. The purpose is to identify the best application that meets the needs of the company, thus knowing the drawbacks that are present in the course of the investigation and therefore give you the solution that the company expects with this research project.